COMBINATION OF PERFORATION AND HEMORRHAGE ACCOMPANYING GASTRODUODENAL ULCER - V. A. AVAKIMYAN; G. K. KARIPIDI; S. V. AVAKIMYAN; O. A. ALUKHANYAN; M. T. DIDIGOV; E. S. BABENKO (Кубанский научный медицинский вестник, 2017)
Aim. Evaluation of different methods of surgical treatment of patients with gastroduodenal ulcer, complicated by a combination of perforation and hemorrhage and the rationale for choosing optimal method of surgical treatment. Materials and methods. The article summarizes the experience of surgical treatment of combined complications of ulcer disease in the form of perforation and hemorrhage. This combination was found in 52 from 753 patients who underwent surgery for ulcer perforation. The hemorrhage arose from a perforated ulcer, and other. The hemorrhage was in the abdomen (5 cases or 0,66%) and in the lumen of the gastrointestinal tract (47 patients or 6,2%). Results. In the surgical treatment of combined complications of gastroduodenal ulcer disease the mortality rate was more than 19%. The most severe patients were those who had free perforated ulcer combined with hemorrhage. Gastric resection was applied at 31,9%. Simple stitching perforated hole ulcers is unacceptable because 2/3 patients with gastroduodenal ulcers have at least two ulcers, one of which is complicated by perforation and hemorrhage. Even at the minimum volume of surgical intervention it is appropriate to perform pyloroplasty according to Judd. Conclusion. The surgery of choice is pyloroplasty according to Judd. Approximately 1/3 of patients have to resort to resection of the stomach, which is dictated by the pathological changes in pyloroduodenal area.